Outcomes of patients failing first-line antiretroviral treatment in a decentralised programme led by nurses in the Democratic Republic of Congo - Gils, Tinne (Department of Public Health and Family Medicine, 2020)
Background: Task-shifting of care and first-line treatment for people living with HIV (PLHIV) from doctors to nurses is feasible, effective and acceptable in sub-Saharan Africa. Since first-line resistance to antiretroviral therapy (ART) is increasing, comprehensive HIV care should be informed by viral load (VL) monitoring to ensure timely detection of treatment failure and switch to second-line ART if appropriate. Patients identified with a first elevated VL (FEVL) enter a cycle with extra counselling sessions, VL re-testing, and potential regimen switch, putting additional strain on scarce human resources. However, identification of treatment failure and its management remains largely doctor-led and there are limited results from programmes with nurse-led management of treatment failure. Health service-delivery in the Democratic Republic of Congo (DRC) is challenging in a weak health system, pressured by epidemics and political unrest. Despite low HIV prevalence in the capital Kinshasa (1.6%), many PLHIV present with advanced disease and early mortality is high. HIV care and treatment, VL testing and second-line switch in decentralised facilities in Kinshasa is exclusively managed by nurses, but results have so far not been documented. Methods Patient outcome data in three primary care facilities in Kinshasa, were routinely collected since ART introduction in 2002 and entered in the national Tier.net database. A protocol (Section A: Study protocol) was developed with detailed methods and procedures for a retrospective analysis of patient outcomes after having had a FEVL (≥1000 copies/ml). The protocol includes analysis of predictors for favourable outcomes (i.e. retained and with VL re-suppressed at 12 months after first high VL or administratively censored or transferred with suppressed VL), and analysis of compliance to existing protocols. The protocol received approval by ethics boards of the Ministry of Health of the DRC and the University of Cape Town. A structured literature review was conducted (Section B: Literature review), critically appraising peer-reviewed publications describing outcomes of PLHIV on ART after first-line failure in sub-Saharan Africa under programmatic conditions. The review included studies where treatment failure and switch were managed by medical doctors, due to paucity of data of nurse-led management of treatment failure. Predictors for outcomes after failure and switch to secondline were also extracted from available literature. A journal-ready manuscript (Section C: Manuscript) presents the findings of the analysis conducted on patients with a FEVL in three decentralised nurse-led facilities in Kinshasa, and predictors for favourable outcomes. Results Of 294 adults with FEVL who did not switch to second-line before confirmatory VL, 82% had a second VL (VL2) done within 24 months of FEVL at a median (interquartile range [IQR]) of 4.0 (3.1-5.6) months) after FEVL. Among patients with VL2 done, 69% had VL2 ≥1000copies/ml, of whom 75% switched to second-line a median of 1.1 (IQR, 0.7-2.0) months after VL2. Among the 85% of patients who were not deceased, LTFU or transferred out by 6 months after second-line switch, 82% had VL6 versus ≤3 months after FEVL and switching 1-3 versus ≤1 month after VL2 ≥ 1000copies/ml were independently associated with lower odds of a favourable outcome. Conclusion Exclusively nurse-managed detection of virologic failure and switch to second-line ART in decentralised health facilities yielded acceptable outcomes in our cohort in urban Kinshasa. Early detection and fast switch can help improve retention and viral suppression following virologic failure. Task-shifting along the viral load cascade is a feasible and safe strategy in settings with limited human resources and growing viral resistance.